IDENTIFIKASI SEKTOR EKONOMI UNGGULAN DI KABUPATEN KOLAKA TIMUR - Muslim, Caesar; Saenong, Zainuddin; Hastuti, Hastuti; Muadsim, Ikrar (Universitas Tanjungpura, 2024)
The purpose of this study was to identify and analyze the leading economic sectors in East Kolaka Regency, Southeast Sulawesi Province. This research uses secondary data obtained from the Central Bureau of Statistics (BPS) of East Kolaka Regency with a time span of 2018 to 2022. The data was analyzed using Location Quotient (LQ) analysis and Klassen typology. The results showed that the Basic Sector consists of four categories: (1) Agriculture, Forestry, and Fisheries; (2) Wholesale and Retail Trade, Rep. Cars and Motorcycles; (3) Adm. Government, Defense, and Compulsory Social Security; and (4) Other Services. In addition, the Klassen Typology Analysis identifies certain economic sectors as advanced. (1) Agriculture, Forestry, and Fisheries Sector; (2) Government Administration, Defense, and Compulsory Social Security; and (3) Other Services.